Faktor Resiko Yang Berhubungan Dengan Hiperemesis Gravidarum Pada Ibu Hamil Trimester I di Puskesmas Langkahan Kab. Aceh Utara Tahun 2023 - Mawarni Mawarni; Zulkarnain Batubara; Rosmega Rosmega (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2024)
Hyperemesis gravidarum is a condition of excessive nausea and vomiting during pregnancy. Thepurpose of this study is to knowsomefactor that associated with the incidence of Hyperemesis Gravidarum in first trimester pregnant women at Puskesmas Langkahan Kab. Aceh Utara , and in this study, three factors were taken,There are age, parity status, and employment. Themethod of this study uses a quantitative method with a cross sectional design. The sample of this study was amounted to 30 people using total sampling method. The Resultsof this study, using the chi-square test, obtained the value of Asymp. Sig on the age variable is 0.964; on the parity variable 0.092; and the employment variable is 0.374. These results indicate that this value is> 0.05, which means there is significant relationship between age, parity and employment with the incidence of hyperemesis gravidarum. Conclusion from the research conducted based on the relationship of factor related to the incidence of hyperemesis gravidarum,general,parity,and work there is a meaningful relationship.